Customer Satisfaction Analysis (Case Study at PT. Bank Rakyat Indonesia (Persero) Kolaka Branch) - Setyawati, Indri; Sunita Firdayana; Almayra; Adhe arya Pramana (International Journal of Management and Education in Human Development, 2022)
This study aims to analyze the customer satisfaction of PT. Bank Rakyat Indonesia (Persero) Kolaka Branch. The analytical tool used is a Cartesian diagram with the object of research, namely customers of PT. Bank Rakyat Indonesia (Persero) Kolaka Branch. These results indicate that the level of customer satisfaction dominates in quadrant A, which means that the level of customer satisfaction is the main priority for the company.